Community ownership models for decentralised renewables in the global south: a review and research agenda - Schneider, Sophia; Abraham, Aakash; Yetano Roche, María (International Journal of Sustainable Energy Planning and Management, 2025)
Community ownership models for decentralised renewable energy (DRE) have been applied in various contexts across global south countries. However, their characteristics, effectiveness and limitations remain understudied. Understanding these ownership models is of interest in the context of bridging the persistent electricity access gap in the global south, particularly present among remote populations, and the imperative to achieve Sustainable Development Goal 7 by 2030. This study addresses this research gap through a scoping literature review and expert interviews. The findings shed light on the diverse definitions of community ownership in the context of decentralised renewables in the global south and on experiences of applying community ownership models in the global south, and identify four recurring themes: regulation, financing, roles and power, and capacities and skills. Through the lens of the multi-level perspective, we discuss the implications of our findings for energy access, socio-economic development policies and initiatives, and research.